2011
DOI: 10.5402/2011/382487
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Demand Factors in Utilization of Professional Care during Childbirth: Perspectives from Yemen

Abstract: Background. Utilization of professional care during childbirth by women in low-income countries is important for the progress towards MDG 5. In Yemen, home births have decreased minimally during the past decades. Objective. The study investigates the influence of socio-demographic, birth outcome and demand factors on women's future preference of a home or institutional childbirth. Method. We interviewed 220 women with childbirth experience in urban/rural Yemen. We performed bivariate chi-square tests and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Women's perceptions of the lack of interaction and listening skills of formally trained staff during childbirth were important findings in this study. Previous work from Yemen has shown that women who experienced an institutional childbirth were less willing to give birth in the same location next time than women who gave birth at home (Kempe et al, 2011). It is noteworthy, however, that in some situations, simple acts on behalf of trained staff were sufficient to meet the need for personal authority of women during childbirth in hospital.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Women's perceptions of the lack of interaction and listening skills of formally trained staff during childbirth were important findings in this study. Previous work from Yemen has shown that women who experienced an institutional childbirth were less willing to give birth in the same location next time than women who gave birth at home (Kempe et al, 2011). It is noteworthy, however, that in some situations, simple acts on behalf of trained staff were sufficient to meet the need for personal authority of women during childbirth in hospital.…”
Section: Discussionmentioning
confidence: 94%
“…The importance of local understanding has been emphasised in attempting to motivate women to seek biomedical care during childbirth (Asowa-Omorodion, 1997;Obermeyer, 2000;Liamputtong et al, 2005;Kempe et al, 2011). Anthropological research has found imbalances in power and knowledge central to women's reluctance to seek biomedical obstetric care, especially when local nonbiomedical resources are viewed negatively (Asowa-Omorodion, 1997;Davis-Floyd, 2003;Berry, 2006;Izugbara et al, 2009).…”
mentioning
confidence: 98%
“…; Kempe et al. ). This approach to care may lead to high levels of dissatisfaction and subsequent distress.…”
Section: Discussionmentioning
confidence: 97%
“…These factors appear to be vital contributors to levels of satisfaction. In the birthing units in Jordan and other Arab countries, healthcare providers (doctors and midwives) usually make decisions without taking the women's wishes into account (Hatamleh et al 2013;Kempe et al 2011). This approach to care may lead to high levels of dissatisfaction and subsequent distress.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between girls’ autonomy and the utilization of healthcare services is reported by antecedent studies. 27,28 A low level of reproductive health literacy and unawareness of available services were other barriers to access reproductive healthcare services stated by the participants. 29,30 …”
Section: Discussionmentioning
confidence: 95%